PENERAPAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT BERBASIS QUIZIZZ TERHADAP KETERAMPILAN MENULIS PESERTA DIDIK - Aryanti, Widya Safitri; Ridwanudin, Dindin (Elementar : Jurnal Pendidikan Dasar, 2024)
The purpose of this study was to determine the effect of the Quizizz-based Cooperative Script learning model on the writing skills of Grade IV students at MI Darul Muqinin. This research was conducted at MI Darul Muqinin West Jakarta in class IV. The method used in this study is a Quasi Experimental Design with a Non-Equivalent Control Group Design. This study took a sample of 26 people in the experimental class and 27 people in the control class. The research instrument was in the form of a pretest learning outcomes test and then a posttest learning outcomes test. From the test scores of students' learning outcomes, it was obtained that both classes were normally distributed and homogeneous. The results of this study indicate that there is an influence of the Quizizz-based Cooperative Script learning model on students' writing skills. This is shown from the acquisition of the average value of the experimental class is higher than the control class, which is equal to 83,31 for the experimental class and 65,48 for the control class. Then from the calculation of the hypothesis test using the t-test obtained a significance of 0,001 < 0,05, then H0 is rejected and H1 is accepted, so it can be concluded that there is an influence of the Quizizz-based Cooperative Script learning model on the writing skills of class IV students MI Darul Muqinin West Jakarta.